Paths of Song : the Lyric Dimension of Greek Tragedy. - Andújar, Rosa (Trends in Classics - Supplementary Volumes Ser., 2018)
Paths of Song: The Lyric Dimension of Greek Tragedy analyzes the multiple and varied evocations of choral lyric in fifth-century Greek tragedy using a variety of methodological approaches that illustrate the myriad forms through which lyric is present and can be presented in tragedy. This collection focuses on different types of interaction of Greek tragedy with lyric poetry in fifth-century Athens: generic, mythological, cultural, musical, and performative. The collected essays demonstrate the dynamic and nuanced relationship between lyric poetry and tragedy within the larger frame of Athenian song- and performance-culture, and reveal a vibrant and symbiotic co-existence between tragedy and lyric. Paths of Song illustrates the effects that this dynamic engagement with lyric possibly had on tragic performances, including performances of satyr drama, as well as on processes of survival and reputation, selection and refiguration, tradition and innovation. The volume is of particular interest to scholars in the field of classics, cultural studies, and the performing arts, as well as to readers interested in poetic transmission and in cultural evolution in antiquity.